Resiliensi pada Remaja yang Terinfeksi HIV/AIDS (ODHA) - Anna Dian Savitri; Purwaningtyastuti Purwaningtyastuti (Faculty of Psychology, Universitas Semarang, 2019)
This study aims to determine the resilience picture of adolescents infected with HIV AIDS. Subjects in this study were adolescents who tested positive for HIV / AIDS, were undergoing ARV treatment and were willing to become research subjects. The informants who supported this research came from volunteers and the leadership of the shelter where the subjects resided. The method used in this research is a qualitative paradigm with a case study approach. Subject and informant data collection through structured interviews, while the analysis technique used uses triangulation of sources, by comparing the analysis of subject data with research informants. The results of this study are high levels of Sy resilience. Aspects of I Have include support and attention from others, Sy prioritizes pleasure and comfort, has a role model, has the drive to be independent, and has experienced health discrimination, gets good education and safety services. Factor I Am includes having an attractive attitude, expressing love through actions, and caring. I Can aspects include being able to express what is felt and thinking, being able to solve problems, being able to control emotions, and being able to foster good relations with others. The subject has good resilience and is able to accept his conditionKeywords: Resilience, Youth, HIV / AIDSDaftar PustakaAzwar, S. 2003. Penyusunan Skala Psikologi. Yogyakarta: Pustaka Pelajar Offset Calhoun, J.F. dan Acocella, J.R. 1995. Psikologi Tentang Penyesuaian dan Hubungan Kemanusiaan. New York : Mc Graw Hill Chaplin, C.B. 1995. Kamus Lengkap Psikologi. (Terjemahan: Kartini Kartono).ed 1. cetakan ke-2. Jakarta: Grafindo Persada.Davidoff. 1991. Psikologi Suatu Pengantar. Jilid 2. Alih Bahasa : Mari Jumiati.Jakarta : Erlangga Gerungan, W.A. 1996. Psikologi Sosial. Bandung : PT Eresco Herdiansyah, Haris. 2015. Metodologi Penelitian Kualitatif untuk Ilmu Psikologi. Jakarta : Salemba Humanika Hurlock, E. 2004. Psikologi Perkembangan. Jakarta : Erlangga Press Kementrian Kesehatan RI (2012) : MEDIAKOM Mengenal, Mencegah Pertumbuhan HIV-AIDS. Jakarta. Komisi Penanggulangan AIDS (KPA), (2003) Strategi Nasional Penanggulangan AIDS, 2003-2007, Menkosesra, KPAN, Jakarta. Kurniawan, Y., & Noviza, N. (2018). Peningkatan Resiliensi pada Penyintas Kekerasan terhadap Perempuan Berbasis Terapi Kelompok Pendukung. Universitas Islam Negeri Walisongo, 2(2), 125 142. http://dx.doi.org/10.21580/pjpp.v2i2.1968 Sarafino. 1998. Health Psikologi : Biopsychosocial Interaction. USA : John Willey and sons Smet, B. 1994, Psikologi Kesehatan. Jakarta : PT Grasindo